Characteristics of non-suicidal self-injury and its associations with gender minority stressors among Hungarian transgender and gender diverse adults - Banu C. Ünsal; Zsolt Demetrovics; Melinda Reinhardt (BMC Psychiatry)
Abstract Background Transgender and gender diverse (TGD) individuals experience gender-related distal (i.e., discrimination, victimization, rejection, non-affirmation) and proximal (i.e., internalized transphobia, expectation of rejection, and identity nondisclosure) stressors, which increase their risk for non-suicidal self-injury (NSSI). Yet, there is a paucity of research examining the prevalence, characteristics, and correlates of NSSI in TGD populations. Methods A convenient sample of Hungarian TGD adults (N = 202; M = 29.60, SD = 10.27; 39.6% gender diverse individuals, 35.6% trans men, 24.8% trans women) took part in an online, questionnaire-based, cross-sectional survey. Gender minority stressors and several aspects of NSSI (i.e., prevalence, frequency, number of methods, and motivations) were assessed. Results Results showed a high lifetime (n = 142, 70.3%) and past-month (n = 48, 33.8%) prevalence of NSSI, with trans men (n = 55, 76.4%) and gender diverse individuals (n = 59, 73.8%) reporting higher lifetime prevalence than trans women (n = 28, 56.0%). Those who engaged in NSSI previously were significantly younger compared to those without NSSI. Structural equation model (SEM), examining the associations among gender minority stressors and functions of NSSI, revealed that proximal stressors mediated the link between distal stressors and intrapersonal functions of NSSI. Regarding interpersonal functions, neither distal nor proximal stressors were significant predictors. Conclusions Findings suggest that trans men and gender diverse individuals, and younger TGD individuals are at greater risk for NSSI. Intrapersonal functions of NSSI and their potential association with proximal stressors should be carefully considered and assessed in clinical practice. Interventions targeting these specific associations should be developed and implemented to provide culturally sensitive care to TGD population.